Purple Ruellia Flower (Ruellia Simplex Wright) Ethanol Extract Lotion as Skin Moisturizer - Hepni Sibagariang; Meliani Dwi Lestari (Science Midwifery, 2021)
Purple ruellia flower is a garden and yard ornamental plant that we often find in our environment. This study aims to determine whether purple ruellia flowers in a certain concentration are able to provide moisture and do not cause skin irritation. Purple ruellia flowers were macerated with 96% ethanol solvent, then ethanol extract of purple ruellia flowers was made with concentrations of 1%, 1.5%, 2%, 25%, and blanks. The results showed that purple ruellia simplex Wright flower ethanol extract lotion could be used as a homogeneous skin moisturizer, at concentrations of 1%, 1.5%, 2%, 2.5% stable in terms of odor changes. The ethanol extract of purple ruellia flower (Ruellia simplex Wright) in a concentration (2.5%) had a water content of (47.3%), almost the same as the comparison lotion on the market (CITRA) of (47.6%) in the "moist" category. , studied moisturizing lotion preparations do not irritate the skin.